PRODUKSI GAS HIDROGEN MENGGUNAKAN METODE ELEKTROLISIS DARI ELEKTROLIT AIR DENGAN KATALIS NaOH - Manurung, Reinaldi; Putri Afisna, Latifa; Gumara Nugrah, Duta; Rainal, Edwa; Juhensen, Jadi; Mahendra, Muhammad Ryan (KURVATEK, 2022)
Hydrogen gas is a gas that can consume or detonate under specific circumstances. In any case, hydrogen can’t be tracked down straightforwardly in nature, since it will undoubtedly water or hydrocarbons. One technique that can be utilized in the partition of hydrogen is utilizing the electrolysis interaction. Subsequently, in this review, the hydrogen gas creation process was done utilizing the electrolysis strategy for water electrolyte with a NaOH impetus. Where the varieties of plates utilized are 5, 6 and 7 plates with each plate being electrolyzed. The impact of plate minor departure from the strain got by utilizing 5 plates with a period of 1,2, and 3 minutes separately was 0.441 Pa, 1.274 Pa, and 2.695 Pa. Then for the 6 plate variety, how much strain with a similar time variety is acquired consecutively 0.548 Pa, 1.401 Pa, and 2.812 Pa. Concerning the 7 plates utilizing a similar time successively and got a strain worth of 0.637 Pa, 1.568 Pa, 2.881 Pa. The impact of plate minor departure from temperature with values acquired utilizing 5 plates with progressive seasons of 1,2, and 3 minutes is 33â„ƒ, 34â„ƒ, 37â„ƒ. Then for the variety of 6 plates utilizing a similar time got the temperature upsides of 33â„ƒ, 35â„ƒ, and 38â„ƒ. While for 7 plates involving a similar time in grouping and getting temperature upsides of 34.4â„ƒ, 39.6â„ƒ, and 42.5â„ƒ.